Rapid Evaluation of the Bioremediation of Fuel Oil in Soil by Gas Chromatography–Laser Ionization Time-of-Flight Mass Spectrometry. (12th December 2017) - Miyagawa, Tomomi; Shimizu, Shiho; Miura, Asa; Fukuyama, Atsuko; Uchimura, Tomohiro
ABSTRACT: Gas chromatography–laser ionization time-of-flight mass spectrometry (GC-LI-TOFMS) was applied to the analysis of fuel oil in soil and soil treated by bioremediation. To demonstrate rapid and selective measurement, only filtered samples after extraction of fuel oil from soil were prepared. The required time for preparing three sample solutions from an oil-contaminated soil sample was only ca. 30 min. The degree of the decrease in the fuel oil in a soil sample by vaporization was confirmed by GC-LI-TOFMS, and after 7 days, the five peak areas arising from the constituents in fuel oil were decreased to between 39 and 79% of their original values. Next, the effect of bioremediation was confirmed by the addition of microbes ( Rhodococcus sp. and Acinetobacter sp. ). As a result, after 7 days, the five peak areas were decreased to between 61 and 81% of the values of the first decreases, after allowing for the effect of vaporization. This method showed sufficient selectivity, robustness, and rapidity for the measurement of oil-contaminated soil treated by bioremediation, which is essential for the evaluation of real environmental remediation.